1992
DOI: 10.1002/jso.2930490209
|View full text |Cite
|
Sign up to set email alerts
|

Search for anti‐metastatic therapy: Effects of phenytoin on B16 melanoma metastasis

Abstract: The ability to metastasize requires that tumor cells be able to degrade matrix. Nontoxic compounds that inhibit matrix digestion might be useful as anti-metastatic agents. We have investigated whether phenytoin, a drug commonly used in clinical practice that inhibits the production of collagenase by some cells, inhibits metastases in a standard animal model of metastasis: In vitro, phenytoin inhibited the proliferative response of B16 F10 melanoma cells to serum-containing media (75% inhibition at 25 microgram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Vernillo et al in 1990 58 found that phenytoin inhibited bone resorption in rat osteosarcoma cells through significant reduction of collagenase and gelatinase activities. But Dyce et al 59 did not find evidence of PHEN’s gelatinase inhibitory activity in B16 melanoma cells in vitro . This may be evidence of tissue-specific activity which has not been investigated any further.…”
Section: Resultsmentioning
confidence: 95%
“…Vernillo et al in 1990 58 found that phenytoin inhibited bone resorption in rat osteosarcoma cells through significant reduction of collagenase and gelatinase activities. But Dyce et al 59 did not find evidence of PHEN’s gelatinase inhibitory activity in B16 melanoma cells in vitro . This may be evidence of tissue-specific activity which has not been investigated any further.…”
Section: Resultsmentioning
confidence: 95%